Cover pricing in the UK construction industry - Brennan, Ross, 1957-; Canning, Louise; McDowell, Raymond (London : SAGE Publications Ltd, 2017)
This case study concerns the themes of price-fixing, legality and ethicality. The context is the UK construction industry, where numerous firms were found guilty of illegal price collusion in 2009. Cover pricing is a concept that is central to the case study. This is the practice of submitting an unreasonably high bid price for a B2B contract with the intention of not winning the business.
Originally published in Brennan, R., Canning, L., & McDowell, R. (2014). Cover Pricing in the UK Construction Industry. Business-to-business marketing (3rd ed., pp. 349351). London: SAGE Publications Ltd. Print. ISBN: 9781446273722.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Price fixing -- Great Britain -- Case studies; Construction industry -- Great Britain -- Case studies